Whole-genome DNA methylation profiling reveals epigenetic signatures in developing muscle in Tan and Hu sheep and their offspring - Yue, Caijuan; Wang, Jiakang; Shen, Yifei; Zhang, Junli; Liu, Jian; Xiao, Aiping; Liu, Yisha; Eer, Hehua; Zhang, Qiao-e (Frontiers in Veterinary Science, 2023)
Introduction The Tan sheep is a popular local breed in China because of its tenderness and flavor. The Hu sheep breed is also famous for its high litter size, and its muscle growth rate is faster than that of Tan sheep. However, the epigenetic mechanism behind these muscle-related phenotypes is unknown. Methods In this study, the longissimus dorsi tissue from 18 6 month-old Tan sheep, Hu sheep, and Tan-Hu F2 generation (6 sheep per population) were collected. After genomic DNA extraction, whole-genome bisulfite sequencing (WGBS) and bioinformatics analysis were performed to construct genome-wide DNA methylome maps for the Tan sheep, Hu sheep and their Tan-Hu F2 generation. Results Distinct genome-wide DNA methylation patterns were observed between Tan sheep and Hu sheep. Moreover, DNA methylated regions were significantly increased in the skeletal muscle from Tan sheep vs. the F2 generation compared to the Hu sheep vs. F2 generation and the Tan sheep vs. Hu sheep. Compared with Hu sheep, the methylation levels of actin alpha 1 (ACTA1), myosin heavy chain 11 (MYH11), Wiskott-Aldrich syndrome protein (WAS), vav guanine nucleotide exchange factor 1 (VAV1), fibronectin 1 (FN1) and Rho-associated protein kinase 2 (ROCK2) genes were markedly distinct in the Tan sheep. Furthermore, Gene Ontology analysis indicated that these genes were involved in myotube differentiation, myotube cell development, smooth muscle cell differentiation and striated muscle cell differentiation. Conclusion The findings from this study, in addition to data from previous research, demonstrated that the ACTA1, MYH11, WAS, VAV1, FN1, and ROCK2 genes may exert regulatory effects on muscle development.